STEM-Based HOTS Digital Assessment Model in Measuring Higher-Order Thinking Skills of Prospective Teacher Students - Dini Ramadhani; Ary Kiswanto Kenedi; Muhammad Febri Rafli; Hanif Harahap; Asna Mardin (Postgraduate, University of Mataram, 2025)
This study aims to develop a valid digital assessment model using a STEM-based approach to effectively measure higher-order thinking skills (HOTS) among prospective elementary school teachers. The research employed a Research and Development (R&D) method, adapted from the Borg & Gall model, involving expert validation, preliminary field testing, and main field testing at Universitas Samudra’s Elementary Teacher Education program. Instrument validity was examined through the Kaiser-Meyer-Olkin (KMO) test and correlation analysis among indicators. The results showed that the developed model achieved high validity, with strong KMO values and significant indicator correlations, confirming its construct soundness. Additionally, the model enabled real-time feedback, enhancing students’ conceptual understanding and application of HOTS in STEM-related tasks. The discussion highlights how integrating technology and STEM principles into assessment design supports more interactive and reflective learning. The model also addressed challenges in traditional HOTS assessment, such as lack of immediacy and contextual relevance. In conclusion, the STEM-based HOTS digital assessment model provides an effective and practical tool for evaluating prospective teachers' higher-order thinking, offering significant implications for improving teacher education and elementary classroom practices.